2009
DOI: 10.1038/jidsymp.2009.12
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species in HaCaT Keratinocytes After UVB Irradiation Are Triggered by Intracellular Ca2+ Levels

Abstract: It is recognized that reactive oxygen species (ROS) are responsible for skin damage due to UVB-radiation (UVB-R). However, the triggering substance(s) for ROS generation after UVB-R is uncertain with respect to the activation of NADPH oxidase (Nox), xanthine oxidase (XOD), and respiratory chain-chain reactions in mitochondria. As a first step in identifying the trigger(s) for UVB-induced ROS generation, we examined the relationship between Ca(2+) levels and ROS generation in HaCaT keratinocytes. UVB-R exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 10 publications
5
46
1
1
Order By: Relevance
“…The peak level of ROS, registered at 2 h, is in accordance with other findings which demonstrated significantly higher rate of ROS production in the early time period after irradiation (0-2 h) (Dhumrongvaraporn and Chanvorachote, 2013;Masaki et al, 2009). The maximum level of apoptosis occurred later (at 4 h), suggesting the implication of the radiation-induced ROS in this process.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The peak level of ROS, registered at 2 h, is in accordance with other findings which demonstrated significantly higher rate of ROS production in the early time period after irradiation (0-2 h) (Dhumrongvaraporn and Chanvorachote, 2013;Masaki et al, 2009). The maximum level of apoptosis occurred later (at 4 h), suggesting the implication of the radiation-induced ROS in this process.…”
Section: Discussionsupporting
confidence: 79%
“…Ryu et al (2010) claim that a pathway linked to leukotriene B4 receptor BLT2 and NADPH oxidase family protein Nox1 might have a crucial role. Others sustain that intracellular Ca 2+ (Masaki et al, 2009) or catalase enzyme in the skin (Heck et al, 2003) might be the trigger for UV-B-induced ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…OH) (Blokhina et al, 2003), are generated in cells via ROS-producing enzymes, such as NADPH oxidase. There is growing evidence that plasma membrane-bound NADPH oxidase is a major source of ROS production induced by UV radiation in keratinocytes (Beak et al, 2004;Park et al, 2006) and that ROS generation requires elevation of intracellular Ca 2+ level in keratinocytes (Goldman et al, 1997;Masaki et al, 2009). ROS are highly reactive and are capable of causing oxidative DNA damage (Ehlers et al, 1999), altering membrane potential (Ehlers et al, 1999), peroxidizing proteins (Perluigi et al, 2010) and lipids (Punnonen et al, 1991), and inducing apoptosis (Clayton et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…UVB radiation is genotoxic and causing extensive cell damage. Many studies reported that UVB radiation induces ROS and leads to cell damage in epidermal keratinocytes (Heck et al, 2003;Masaki et al, 2009). The present results demonstrated that the recombinant protein of EC-SOD had a scavenging activity reached to 30% against H 2 O 2 -induced ROS compared with 27% activity of B. hamifera extract (Piao et al, 2012) at the same concentration of 200 μg mLG 1 and 67% activity for N-acetyl cysteine (NAC).…”
Section: Discussionmentioning
confidence: 99%